Zavegepant nasal spray for the acute treatment of migraine: A Phase 2/3 double‐blind, randomized, placebo‐controlled, dose‐ranging trial. Issue 9 (14th October 2022) - Croop, Robert; Madonia, Jennifer; Stock, David A.; Thiry, Alexandra; Forshaw, Micaela; Murphy, Abigail; Coric, Vladimir; Lipton, Richard B.
Abstract: Objective: Evaluate the efficacy, safety, and tolerability of zavegepant nasal spray in the acute treatment of migraine. Background: Calcitonin gene‐related peptide‐targeting agents are a novel class of therapeutics for migraine, but none are currently available as a nonoral option for acute treatment. Zavegepant, a high‐affinity, selective, and structurally unique calcitonin gene‐related peptide‐receptor antagonist in late‐stage development, is formulated as a nasal spray for the acute treatment of migraine. Methods: This randomized, dose‐ranging, placebo‐controlled, Phase 2/3 trial in adults aged ≥18 years with migraine (NCT03872453) was conducted at US study sites. Participants were randomized by an interactive web response system and treated a single attack of moderate to severe pain intensity with zavegepant nasal spray 5, 10, 20 mg, or placebo. Coprimary efficacy endpoints were pain freedom and freedom from the most bothersome symptom at 2 h postdose. Results: Of the 1673 participants aged 18 to 79 years who were randomized, 1588 were treated with study medication, and 1581 (mean age 40.8 years, 85.5% female) were analyzed for efficacy: zavegepant 5 mg ( n = 387), 10 mg ( n = 391), 20 mg ( n = 402), and placebo ( n = 401). Zavegepant 10 and 20 mg were more effective than placebo on the coprimary endpoints of pain freedom at 2 h postdose (placebo: 15.5% [98.3% confidence interval (CI), 11.1, 19.8]; 10 mg: 22.5% [98.3% CI, 17.5, 27.6; p = 0.0113]; 20 mg: 23.1% [98.3% CI, 18.1, 28.2; p = 0.0055]) and freedom from the most bothersome symptom at 2 h postdose (placebo: 33.7% [98.3% CI, 28.0, 39.3]; 10 mg: 41.9% [98.3% CI, 36.0, 47.9; p = 0.0155]; 20 mg: 42.5% [98.3% CI, 36.6, 48.4; p = 0.0094]). Findings for the 5 mg dose were not significant. The most common treatment‐emergent adverse events with zavegepant 10 and 20 mg and placebo were dysgeusia (13.5% to 16.1% vs. 3.5%), nausea (2.7% to 4.1% vs. 0.5%), and nasal discomfort (1.3% to 5.2% vs. 0.2%). Most adverse events were mild or moderate and resolved without treatment. There was no signal of hepatotoxicity. Conclusion: Zavegepant nasal spray, in single doses of 10 or 20 mg, was effective for the acute treatment of migraine, with a favorable safety profile. Additional research is needed to confirm its potential as a nonoral medication for the acute treatment of migraine.